Analysis of Student Satisfaction Levels with the Quality of Academic Services - Erny Rachmawati; Hadi Pramono; Suyoto Suyoto (International Journal of Economics and Management Research, 2023)
The problem of the quality of academic services for each faculty is different. The aim of this research is to describe the level of student satisfaction regarding the quality of academic services based on the Parasuraman dimensions. The assessment used a 5-point Likert scale of satisfaction with lecturers with the respondents being students from three study programs, namely the faculties of Economics and Business, Psychology and Law, with 192 students. The results of research on Tangible students feel satisfied with the faculties of Economics and Business, Psychology and Law. At Emphaty, students feel satisfied with the Faculty of Economics and Business and the Faculty of Law. At the Psychology faculty, students feel less satisfied. Regarding Reliability, students feel satisfied with the Faculty of Economics and Business and the Faculty of Law. At the Psychology faculty, students feel less satisfied. Regarding Responsiveness, students feel satisfied with the Faculty of Economics and Business and the Faculty of Law. At the Psychology faculty, students feel dissatisfied. In Assurance, students feel satisfied with the Faculty of Economics and Business and the Faculty of Law. At the Psychology faculty, students feel dissatisfied. This research is very useful for improving the quality of academic services.